Analisis Kemampuan Sosial Emosional pada Anak Menggunakan Digital Game Based Learning di TK PGRI Pakumbulan - Sulistyaningsih, Wahyu; Saputro, Bagus Ardi; Purnamasari, Iin (Universitas PGRI Semarang, 2025)
This study aims to describe children's social emotional abilities using Digital Game Based Learning at PGRI Pakumbulan Kindergarten, Buaran District, Pekalongan Regency. The sample consisted of 21 class A students of PGRI Pakumbulan Kindergarten in the 2022-2023 academic year, data collection in this study used observation, interview, and documentation techniques. While the analysis technique used was Triangulation. The results of the study showed that there was an increase in children's social emotional abilities because they used Digital Game Based Learning, while the learning media used were visual media, such as simple games, original images, and the use of laptops as learning media